Effect of diazotrophic bacteria as phosphate solubilizing and indolic compound producers on maize plants (2013)
Phosphorus is limiting for growth of maize plants, and because of that use of fertilizers like Rock Phosphate has been proposed. However, direct use of Rock Phosphate is not recommended because of its low availability, so it is necessary to improve it. In this study, a group of diazotrophic bacteria were evaluated as phosphate-solubilizing bacteria, for their production of indolic compounds and for their effects on growth of maize plants. Strains of the genera Azosporillum, Azotobacter, Rhizobium and Klebsiella, were quantitatively evaluated for solubilization of Ca3(PO4)2 and rock phosphate as a single source of phosphorous in SRS culture media. Additionally, the phosphatase enzyme activity was quantified at pH 5.0, 7.0 and 8.0 using p-nitrophenyl phosphate, and production of indolic compound was determined by colorimetric quantification. The effect of inoculation of bacteria on maize was determined in a completely randomized greenhouse experiment where root and shoot dry weights and phosphorus content were assessed. Results showed that strain C50 produced 107.2 mg .L-1 of available-P after 12 days of fermentation, and AC10 strain had the highest phosphatase activity at pH 8 with 12.7 mg of p-nitrophenol mL .h-1. All strains synthetized indolic compounds, and strain AV5 strain produced the most at 63.03 µg .mL-1. These diazotrophic bacteria increased plant biomass up to 39 % and accumulation of phosphorus by 10%. Hence, use of diazotrphic phosphate-solubilizing bacteria may represent an alternative technology for fertilization systems in maize plants.